Researcher Reflexivity in the Post-Positivism Paradigm: A Systematic Literature Review - Disa Sri Ilma; Andri Ani Suryawijaya; Yulius Efendi; Wahyu Arohman Hidyataullah; Riska Meisyi Putri; Anggia Pratiwi; Elfa Eriyani (Al-Qalam Institue, 2026)
Researcher reflexivity has become an important principle within the post-positivist paradigm because it enhances transparency, integrity, and the quality of scientific inquiry. This study aims to analyze and synthesize the development of research on researcher reflexivity within the post-positivist paradigm, focusing on its conceptual development, implementation practices, contributions to research quality, and challenges in its application. This study employed a qualitative research design using the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. Relevant literature published between 2022 and 2026 was identified, selected, and analyzed through a thematic synthesis approach to explore patterns and emerging themes related to researcher reflexivity. The findings indicate that reflexivity has developed beyond a personal reflective process into a methodological strategy that strengthens research trustworthiness through credibility, dependability, confirmability, and transferability. The study implies that integrating reflexivity practices systematically can support more transparent, accountable, and rigorous research processes. Furthermore, this synthesis provides a conceptual foundation for researchers and scholars to develop improved methodological frameworks that recognize the researcher’s role in knowledge construction.